KELAS KUAT KAYU TUMIH (Combretocarpus rotundatus (Miq.) Danser) BERDASARKAN BAGIAN BATANG (The the physical and mechanical Properties of Tumih Wood Based on Section Stem) - Gimson Luhan; Herwin Joni; Johansyah; Yanciluk; Ahmad Mujaffar (HUTAN TROPIKA, 2019)
Tumih wood (Combretocarpus rotundatus (Miq.) Danser) is classified as an unknown type of wood which is widely grown in peat swamp forests in Central Kalimantan. This study aims to analyze the physical properties and mechanical properties of wood in axial and radial directions so that they can be utilized properly. The results of the study resulted in fresh water content and dry air content of wood air, each of which was 71,58% and 19,33%, kiln dry weight 0,72, tangential shrinkage 9,68%, radial shrinkage 5,02% and longitudinal shrinkage 0,19%. Testing of mechanical properties resulted in a flexural firmness of 618,33 kg/cm2, compressive strength parallel to the fiber 333,27kg/cm2, shear constancy 92,02 kg/cm2, hardness 355,60 kg/cm2, and stiffness at 19,50kg/cm2. Based on the Indonesian Wood Construction Regulations Standard (PKKI) NI 5-1961 tumih wood is included as a strong class III of Indonesian wood, so it is quite well used for home building raw materials, beams, floor and wall boards, door/window frames, and furniture.